Design Study of the Crossed Field Antenna - W. Salman, Jamal; M. K. Tashan, Tariq (Journal of Engineering and Sustainable Development, 2006)
Besides the fast development in the technology of the electronics world, there is another development in the concepts and principles of antenna work. This paper presents mathematical expressions for the main features of the cross-field antenna CFA, like electric field E, magnetic field H, and the Poynting vector S. These expressions are basically derived by considering the principle of two point charges in the space throw measuring the potential at far point, leading to the electric field and magnetic field forms of CFA.